2022
DOI: 10.1007/s40618-022-01900-9
|View full text |Cite
|
Sign up to set email alerts
|

Sellar and parasellar lesions in the transition age: a retrospective Italian multi-centre study

Abstract: Background Sellar/parasellar lesions have been studied in the adult and paediatric age range, but during the transition age their epidemiology, clinical manifestations, management and treatment outcomes have been poorly investigated. Materials and methods An Italian multicentre cohort study, in which hospital records of patients with diagnosis of sellar/parasellar lesions during the transition age and young adulthood (15–25 years), were reviewed in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Blood tests for hormonal assays and testicular US were performed at each evaluation. Transition age was defined as the phase between the end of puberty and young adulthood: therefore, we included in the transition age group subjects who had achieved Tanner stage V and completed linear growth ( 32 , 33 ); subjects ages 26 years and older were included in the adult group.…”
Section: Methodsmentioning
confidence: 99%
“…Blood tests for hormonal assays and testicular US were performed at each evaluation. Transition age was defined as the phase between the end of puberty and young adulthood: therefore, we included in the transition age group subjects who had achieved Tanner stage V and completed linear growth ( 32 , 33 ); subjects ages 26 years and older were included in the adult group.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from scattered case reports, only two studies have reported the clinical presentation of patients with pituitary gigantism diagnosed during the transition age [ 39 , 41 , 42 ]: a single-centre study by Colao et al conducted on 13 patients diagnosed between 15 and 20 years, and a multi-centre study by Rostomyan et al investigating more than 200 patients with a wider age at diagnosis (median 21 years, interquartile range 15.5–27) [ 39 ]. Tall stature is usually the first clinical sign that leads to medical attention, thus initiating the diagnostic process for gigantism.…”
Section: Clinical Presentation Of Gigantism During the Transition Agementioning
confidence: 99%